Methodes numeriques avancees en vibroacoustique basses et moyennes frequences - Ohayon, Roger; Soize, Christian (European Journal of Computational Mechanics, 1999)
This paper presents a synthesis of modeling and associated numerical methods for the prediction of linear vibrations of arbitrary structural-acoustic tridimensional systems constituted of a structure containing an internal dissipative acoustic fluid and surrounded by an external inviscid acoustic fluid occupying an unbounded domain. The model includes wall acoustic impedances. For low-frequency vibroacoustic problems, we present reduced matrix models based on Ritz-Galerkin projection of the finite element model using appropriate modal basis. Finally, for medium-frequency vibroacoustic problems, we present the finite element model and solving methods, i.e. a two time scales procedure and a method of construction of appropriate reduced matrix models.